2016
DOI: 10.1021/acs.jced.5b00658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkyl Chain Branching on Physicochemical Properties of Imidazolium-Based Ionic Liquids

Abstract: The branched ionic liquids (ILs) 1-(iso-alkyl)-3-methylimidazolium bis­[(trifluoromethane)­sulfonyl]­amide ([(N – 2)­mC N‑1C1im]­[NTf2] with N = 3–7) were synthesized and their physicochemical properties characterized and compared with the properties of linear ILs 1-(n-alkyl)-3-methylimidazolium bis­[(trifluoromethane)­sulfonyl]­amide ([C N C1im]­[NTf2] with N = 3–7). For N = 4–7, the density of the branched IL [(N – 2)­mC N–1C1im]­[NTf2] is the same as that of its linear analogue [C N C1im]­[NTf2] within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 76 publications
14
65
1
Order By: Relevance
“…Figure a shows the densities of the synthesized RTILs. The densities of imidazolium based ILs are decreasing with increasing length of the alkyl chain . As expected from these results, the densities of the ammonium ILs decrease in the order [N 1123 ] + >[N 1224 ] + >[N 1134 ] + >[N 2225 ] + and thus with increasing cation volume V m + .…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Figure a shows the densities of the synthesized RTILs. The densities of imidazolium based ILs are decreasing with increasing length of the alkyl chain . As expected from these results, the densities of the ammonium ILs decrease in the order [N 1123 ] + >[N 1224 ] + >[N 1134 ] + >[N 2225 ] + and thus with increasing cation volume V m + .…”
Section: Resultssupporting
confidence: 70%
“…The melting point ( T m ) of a molecule is determined by the strength of its crystal lattice, which is influenced by three factors: molecular symmetry, conformational degrees of freedom, and intermolecular forces . For ILs, the effect of varying branching, length, and position of alkyl chains, as well as the influence of the symmetry of the anions and cations on T m was investigated . In general, combining a cation with large size, low symmetry and flexible substituents and an anion with low symmetry and good charge distribution results in an IL with a low melting point.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, imidazolium‐based ILs are used in our work due to their higher selectivity and lower viscosity. Since the selectivity of imidazolium‐based ILs is inversely proportional to their viscosity which is proportional to the length of cation side chain, [BMIM][Ac] is suggested as the solvent to separate the mixture of acetonitrile and ethanol. In order to verify the outstanding separation performance of [BMIM][Ac], the vapor–liquid equilibrium (VLE) data of the acetonitrile + ethanol +[BMIM][Ac] were determined at 101.3 kPa in the following section.…”
Section: Ionic Liquid Screenmentioning
confidence: 99%
“…These ILs, generally named as surface‐active ILs (SAILs), have been extensively studied. It has been demonstrated that the length of the alkyl chain, type of group head, and the nature of counterions affect the self‐aggregation, leading to modification in critical micelle concentrations (cmc), size, shape, and aggregation number ( N agg ), among others …”
Section: Introductionmentioning
confidence: 99%